ANALYSIS OF THE USE OF ZEOLITE AS A SUBSTITUTE FOR SOME OF THE COARSE AGGREGATE IN POROUS CONCRETE - TEGUH SIANTURI; LYDIA DARMIYANTI; INDRIASARI (CV KULTURA DIGITAL MEDIA, 2025)
Rapid urban development increases water runoff due to impervious areas. Porous concrete is an environmentally friendly solution because it absorbs water and preserves groundwater. This study examines the use of porous zeolite as a partial substitute for coarse aggregate to improve the mechanical and environmental performance of porous concrete, particularly in areas with light traffic and sustainable water management requirements. The compressive strength of concrete with 0% zeolite stone composition reached 18.66 MPa (7 days), 22.60 MPa (14 days), and 25.60 MPa (28 days), exceeding all SNI 2847:2019 requirements. The compressive strength of concrete with 15% zeolite stone reached 16.06 MPa (7 days), 20.82 MPa (14 days), and 22.18 MPa (28 days), but none of them met the minimum limit of SNI 2847:2019. The compressive strength of concrete with 30% zeolite aggregate reached 16.07 MPa (7 days), 20.83 MPa (14 days), and 22.20 MPa (28 days), but none of them met the minimum standard of SNI 2847:2019.